Finite automaton actions of free products of groups - Fedorova, M.; Oliynyk, A. (Algebra and Discrete Mathematics, 2017)
It is shown that for groups G and H that act faithfully by finite state automorphisms on regular rooted trees their free product G∗H admits a faithful action by finite state automorphisms on some regular rooted tree.